2009
DOI: 10.1051/0004-6361/200811282
|View full text |Cite
|
Sign up to set email alerts
|

Revealing X-ray obscured quasars in SWIRE sources with extreme mid-IR/optical flux ratios

Abstract: Recent works have suggested that selection criteria based on mid-IR properties, i.e. extreme colors and bright flux levels, can be used to reveal a population of dust-enshrouded, extremely-luminous quasars at z ∼ 1-2. However, the X-ray spectral properties of these intriguing objects still remain largely unexplored. We have performed an X-ray study of a large sample of bright mid-IR (F 24 μm > 1.3 mJy) galaxies showing an extreme MIR/Optical flux ratio (F 24 μm /F R > 2000) in order to confirm the presence of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
91
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(109 citation statements)
references
References 98 publications
(170 reference statements)
17
91
1
Order By: Relevance
“…However, because of the lack of X-ray spectroscopy the fraction of Compton-thick sources cannot be readily quantified. Based on brighter sources with X-ray spectroscopy in the GOODS (Georgantopoulos et al 2011), AEGIS (Georgakakis et al 2010) and SWIRE fields (Lanzuisi et al 2009), the fractions of Compton-thick sources found among IR-excess AGN range between 0% and 50%. Another widely applied mid-IR method for the selection of Compton-thick AGN ) relies on low X-ray to IR ratios.…”
Section: Discussionmentioning
confidence: 99%
“…However, because of the lack of X-ray spectroscopy the fraction of Compton-thick sources cannot be readily quantified. Based on brighter sources with X-ray spectroscopy in the GOODS (Georgantopoulos et al 2011), AEGIS (Georgakakis et al 2010) and SWIRE fields (Lanzuisi et al 2009), the fractions of Compton-thick sources found among IR-excess AGN range between 0% and 50%. Another widely applied mid-IR method for the selection of Compton-thick AGN ) relies on low X-ray to IR ratios.…”
Section: Discussionmentioning
confidence: 99%
“…The columns are: (1) X-ray ID as in Table 1; (2) HST ID from the catalogue of Giavalisco et al (2004) and Grazian et al (2006) for the CDF-N and CDF-S respectively; (3) HST coordinates (J2000); (4) z-band AB magnitude (F850LP) (5) comment on morphology. Lanzuisi et al (2009) have recently performed an X-ray study of luminous DOGs (F 24 μm /F R > 2000 and F 24 μm > 1.3 mJy) in the Spitzer Wide-Area Infrared Extragalactic (SWIRE) survey. An area of 6deg 2 out of the total 50 deg 2 of the SWIRE survey has been surveyed by XMM-Newton or Chandra.…”
Section: Overall Propertiesmentioning
confidence: 99%
“…It is also worth noting that, among the EXO50 sources defined here, about 40% can be classified as EDOGs (∼ 60% excluding the BL Lac objects). Unfortunately, two of our EXO50 EDOGs are still unidentified, preventing us to make a proper comparison with the work of Lanzuisi et al (2009). We can only say that the absorption properties of the only identified EXO50 EDOG (source number 5) are fully consistent with the main results obtained from Lanzuisi et al (2009): the source is an absorbed QSO with an intrinsic absorbing column density ∼ 3×10 22 cm −2 .…”
Section: The Relation Between Exo50 Objects and Edogsmentioning
confidence: 83%
“…These 3 sources can be classified as Extreme Dust Obscured Galaxies (EDOGs; f 24 µm / f R 2000; Lanzuisi et al 2009), i.e. extreme examples of Dust Obscured Galaxies (DOG, f 24 µm / f R 1000 see Dey et al 2008), a class of galaxies firstly discovered with the Spitzer Space Telescope.…”
Section: The Relation Between Exo50 Objects and Edogsmentioning
confidence: 99%
See 1 more Smart Citation